The Role of Pentahelix Element Stakeholders in the Development of Sungai Lisai Village as A Remote Indigenous Community - Byandra, Genta; Yogopriyatno, Jatmiko; Hardayani, Yorry (Indonesian Journal of Social Science Research, 2024)
Efforts to develop remote villages frequently face complex challenges that require multi-stakeholder collaboration. This research examines the development efforts of Sungai Lisai Village, located in the Kerinci Seblat National Park area of Lebong Regency, Bengkulu, as a Remote Indigenous Community (KAT) using the Pentahelix model. The research objective is to identify stakeholder involvement in Pentahelix elements and analyze their respective roles in the context of village development. The research method used a descriptive qualitative approach with data collection through interviews, document analysis, and direct observation. Data analysis in this study used the Miles and Huberman interactive model. The results showed the involvement of stakeholders from four Pentahelix elements, namely: government (Pemda, Dinsos, PUPR, TNI AD), community (village institutions, residents, NGOs), academics (Bengkulu University), and media (RB TV, RMOL Bengkulu, Bengkulu Ekspress), while business elements have not been identified. Each stakeholder has a specific role, but the synergy between elements is still not very strong. The research also revealed the rejection of the proposal to recognize Sungai Lisai Village as KAT by the Ministry of Social Affairs in 2022, despite ongoing empowerment efforts. The recommendations based on the research results include strengthening collaboration between stakeholders, increasing the capacity of local communities, developing an integrated evaluation and monitoring system, and focusing on improving village accessibility. Thus, the Pentahelix approach can be more effective in supporting the development of Sungai Lisai Village, regardless of its status as KAT or not.